A Reconfigurable WiMAX Antenna for Directional and Broadside Application - M. Jusoh; M. F. Jamlos; M. R. Kamarudin; T. Sabapathy (International Journal of Antennas and Propagation)
A novel reconfigurable compact patch array antenna for directional and broadside application is proposed. The presented antenna has successfully been able to function for directional beam at 320° or 35° and divisive broadside beam at 43° and 330°. This is realized in the unique form of aperture coupled spiral feeding technique and positioning of the radiating elements at 0°, 90,° and 180°. The switchable feature is effectively performed by the configuration of three PIN diodes. All PIN diodes are positioned at the specific location of the aperture coupled structure. It is discovered in simulation that the switches can be represented with a copper strip line or touchstone (TS) block . The proposed antenna design operates at 2.37 GHz to 2.41 GHz and has a maximum gain of 6.4 dB and efficiency of 85.97%. Such antenna produces a broadside HPBW with a wider bandwidth covering from −90° to 90° compared to the normal microstrip antenna which could only provide HPBW of −50° to 50°. Moreover, the proposed antenna has small physical dimension of 100 mm by 100 mm. The simulation and measurement results have successfully exhibited the idea of the presented antenna performance. Therefore, the antenna is sufficiently competent in the smart WiMAX antenna application.